Roles of tolazoline hydrochloride in deformity prevention and control - Garg, B S; Mathur, J S; Tyagi, N K (Indian Journal of Community Health, 1994)
Management of primary and secondary deformities, In the field Is a mqJor difficulty faced by the peripheral health worker. This paper describes a simple method for the correction of deformities. Ill patients with clawing of fingers, 111 patients with neuritis and 54 cases with trophic ulcers were administered perineural injections of Tolazoline hydrochloride. The Improvement in mobility In claw flngers'ranged from 89.5 to 92.1 % Healing of ulcers and improvement In sensory loss Is marked with Tolazoline Injections. This method Is found to be qffecthe in the field conditions.